Point-of-care detection of SARS-CoV-2 antigen among symptomatic vs. asymptomatic persons: Testing for COVID-19 vs. infectivity - Neukam, Karin (2022)
Background: Management of the coronavirus disease 2019 (COVID-19) pandemic caused by a novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) requires rapid and simple methods to detect COVID-19 patients and identify potential infectors. This study aimed to evaluate the utility of a point-of-care (PoC) rapid antigen diagnostic test (Ag-RDT) in these settings. Patients and methods: Individuals who consecutively presented for SARS-CoV-2 testing at a tertiary care center in Buenos Aires, Argentina, underwent PoC Ag-RDT testing and real-time RT-PCR (qRT-PCR) on the same day during June 2021. Results: Of 584 included subjects, 108 (18.5%) were symptomatic for COVID-19 while the remaining presented for miscellaneous reasons unrelated to possible or confirmed contact with a SARS-CoV-2-infected individual. A positive Ag-RDT result was obtained in 26 (24.1%) symptomatic and 7 (1.5%) asymptomatic persons (p < 0.001), which was concordant with qRT-PCR in 105/108 [97.2%, Cohen's kappa coefficient (κ) = 0.927] symptomatic and 467/476 (98.1% κ = 0.563) asymptomatic participants, with a positive percentage agreement (PPA; 95% confidence interval) of 89.7% (71.5–97.3%) and 42.9% (18.8–70.4%), respectively. None of the 11 false-negative diagnoses showed a Ct-value ≤20. Considering only failures with a Ct-value below 31 as hypothetical infectivity threshold of 105 SARS-CoV-2 RNA copies/mL, concordance was observed in 98.1% (κ = 0.746) in the asymptomatic population, accounting for a PPA of 66.7% (30.9–91%). Conclusions: PoC Ag-RDT accurately detected active SARS-CoV-2 infection and showed acceptable diagnostic performance in asymptomatic persons potentially spreading infectious virus. Ag-RDT may therefore be useful to slow down or stop transmission by enabling adequate decisions on isolation at a public health level.